An Optimized Procedure for the Site-Directed Labeling of NGF and proNGF for Imaging Purposes - Di Matteo, Pierluigi; Calvello, Mariantonietta; Luin, Stefano; Marchetti, Laura; Cattaneo, Antonino (Frontiers in Molecular Biosciences, 2017)
Neurotrophins are growth factors of fundamental importance for the development, survival and maintenance of different neuronal and non-neuronal populations. Over the years, the use of labelled neurotrophins has helped in the study of their biological functions, leading to a better understanding of the processes that regulate their transport, traffic and signalling. However, the diverse and heterogeneous neurotrophin labelling strategies adopted so far have often led to poorly reproducible protocols and sometimes conflicting conclusions. Here we present a robust, reliable and fast method to obtain homogeneous preparations of fluorescent- proNGF and NGF with 1:1 labelling stoichiometry. This strategy is well suited for several applications, ranging from advanced imaging techniques such as single particle tracking, to analyses that require large amounts of neurotrophins such as in vivo monitoring of protein biodistribution. As a proof of the quality of the labelled NGF and proNGF preparations, we provide a quantitative analysis of their colocalization with proteins involved in the signalling endosome function and sorting. This new analysis allowed demonstrating that proNGF localizes at a sub-population of endosomes not completely overlapped to the one hosting NGF.